1-g Shaking table tests to determine the behavior of geosynthetic reinforced soil walls under seismic loads. (September 2021) - Başbuğ, Ercüment; Cengiz, Cihan; Güler, Erol
Abstract: Geosynthetic reinforced soil structures are widely used to support and enable transportation infrastructure. Given the importance of the transportation infrastructure within the context of disaster resilience, it is crucial to fully understand the response of the elements which constitute and support the infrastructure assets. This study presents and discusses the results of four heavily instrumented large scale geosynthetic reinforced soil walls which were subjected to seismic loading under 1-g conditions. The walls were constructed with different reinforcement arrangements, backfill materials, and batter angles to study the effects of these parameters on the behaviour and seismic performance of model walls. The test results indicate an interplay with the wall response and Arias Intensity which is an earthquake intensity measure.